2018
DOI: 10.1089/bfm.2018.0031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pacifier Use on Transition Time from Gavage to Breastfeeding in Preterm Infants: A Randomized Controlled Trial

Abstract: In this study, we determined that the method of giving pacifiers to preterm infants during gavage feeding reduced the infants' transition period to oral feeding and the duration of hospital stay. In addition, the pacifiers could be used during gavage feeding and in the transition from gavage to oral/breastfeeding in preterm infants to encourage the development of sucking ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
2
28
0
1
Order By: Relevance
“…In a study conducted by Say et al in 2018 on the effect of pacifier on the transition time from gavage to breastfeeding in preterm infants, they found that the transition time to full breastfeeding was significantly shorter in the pacifier group compared to the control group. They concluded that giving pacifiers to preterm infants during gavage feeding can reduce the duration of transition to oral feeding and the duration of hospitalization [ 11 ]. These results are consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Say et al in 2018 on the effect of pacifier on the transition time from gavage to breastfeeding in preterm infants, they found that the transition time to full breastfeeding was significantly shorter in the pacifier group compared to the control group. They concluded that giving pacifiers to preterm infants during gavage feeding can reduce the duration of transition to oral feeding and the duration of hospitalization [ 11 ]. These results are consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Younesian et al noted that due to the combined use of the two methods, it is not clear whether NNS or oral massage is more effective [ 1 , 8 ]. In studies conducted by Say et al [ 11 ] and Mohammadi PirKashani et al [ 12 ], these two methods have been presented separately and have not been compared with each other. It is not clear which method is better and more suitable for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Of the ten studies included, five covered term infants [8][9][10][11]18] and five preterm infants [13,[19][20][21][22] (Table S1). In the studies with term infants, the intervention groups were instructed not to offer pacifiers during hospital stay or longer (up to 3 months).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These results are controversial, in that breastfeeding, breast milk, and glucose/sucrose administration were found to be more effective [ 11 ]. In addition, when using a pacifier, a shortened time to transition to full breastfeeding, to the time to discharge, and to oral feeding is observed [ 12 , 13 ]. For preterm infants, the pacifier has no effect on hospital stay, but their transition to full enteral or bottle feeds was easier [ 14 ].…”
Section: Introductionmentioning
confidence: 99%